2021
DOI: 10.3389/fneur.2021.651867
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Fibrin Degradation Products at Admission With Acute Ischemic Stroke Correlate With the NIH Stroke Scale Score 1 h After Intravenous Thrombolysis

Abstract: Background: Fibrin degradation products (FDPs) are fragments released by the plasmin-mediated degradation of fibrinogen or fibrin. Whether plasma levels of these fragments can predict the thrombolytic effect of recombinant tissue plasminogen activator (r-tPA) remains unknown.Methods: We performed a hospital-based study of patients with acute ischemic stroke (AIS) to explore the relationship between FDP levels at admission and the NIH Stroke Scale (NIHSS) score 1 h after thrombolysis treatment. In this retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Several studies have examined the long-term prognosis of AIS following intravenous thrombolysis or biomarkers to predict intracranial bleeding, while few studies have examined the early response to r-tPA ( 31 , 32 ). In our research, a good response to thrombolysis was observed in 268 patients (38.29%), the ratio is also similar to the results of the previous studies ( 33 , 34 ). Our findings provide several novel observations.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have examined the long-term prognosis of AIS following intravenous thrombolysis or biomarkers to predict intracranial bleeding, while few studies have examined the early response to r-tPA ( 31 , 32 ). In our research, a good response to thrombolysis was observed in 268 patients (38.29%), the ratio is also similar to the results of the previous studies ( 33 , 34 ). Our findings provide several novel observations.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, patients in this study were not restricted to those who received IVT and the blood sample was collected within 72 h after stroke ( 26 ). Zhu et al found that the admission FDP levels correlated with the NIHSS score 1 h after IVT ( 11 ). However, they excluded patients who have large vessel occlusion and underwent endovascular thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had demonstrated that increased FDP levels 2 h post-IVT were associated with PH ( 9 , 10 ). A recent study found that the admission FDP levels were negatively associated with early thrombolytic effect ( 11 ). Nevertheless, few studies focused on the relationships among the admission FDP level, PH, and the 90-day outcome after IVT in patients with AIS.…”
Section: Introductionmentioning
confidence: 99%
“…We retrospectively conducted an analysis using a cohort of AIS patients who received intravenous thrombolysis with r-tPA between January 2019 and October 2020 at the Beijing Tiantan Hospital. The inclusion and exclusion criteria were previously reported by Zhu et al (2021) . Briefly, patients were recruited if they met the following criteria: diagnosis with AIS through magnetic resonance imaging or computed tomography and admittance to the emergency department within 4.5 h of symptom onset.…”
Section: Methodsmentioning
confidence: 99%